Evaluación de Extractos Vegetales y Bioinsecticidas Sobre Poblaciones de Spodoptera frugiperda y Elasmopalpus lignosellus en Maíz - Ortiz, Teddy Landívar; Navarrete, Eduardo Colina; Arteaga, Carlos Castro; Aragoné, Danilo Santana; Vásquez, Guillermo García; Castro, Oscar Mora; Vélez, Martha Uvidia; Cabezas, Miguel Goyes (European Scientific Journal, ESJ, 2017)
The research was carried out on the Property “El Cartan” that is located in Km 4 way at Puebloviejo-Ventanas, county of Los Ríos. A test was conducted on the hybrid corn DK-1040. This test measures the response of the larvae of insects Spodoptera frugiperda and Elasmopalpus lignosellus to the application of dose of biological and organic insecticides. Also, the most appropriate dose in products was determined with an economic analysis. The experimental design used was random complete blocks with seven treatments and three replicates. The variables evaluated are: percentage of larvae control, number of larvae per plant, corn damage, and yield for hectare. The evaluated variables were subjected to the analysis of variance, and Tukey test was applied to 95 % probability. The analyzed results were determined to apply Neem (Azadirachtina indica) in dose of 1,0 L ha -1 . It diminishes the populations of S. frugiperda and E. lignosellus in relationship to the other active matters applied in the test. Higher doses lead to migration of pests to nearby hosts. The highest yield per hectare was found in the Neem 1.0 L ha-1 treatment with 8,940 kg ha-1.